(untitled) - Price, John Ellis (New York, 2012)
The book includes many real-world examples, high-interest problems and activities, in-text help and practice, and classroom-tested dynamic pedagogy. With the addition of McGraw-Hill’s Connect Accounting, the new edition includes more technology support than ever before.
Keywords: Accounting,Kế toán